BR-174 e seu contexto no desenvolvimento regional: dos investimentos voltados para o desenvolvimento regional às contradições em sua organização espacial - Macieira, Mirocem Beltrão (2016)
The research is to screen the state of Roraima and its current socio-formatting, its urban interconnection, and the process of urbanization along the BR-174. It is known that major changes occurred in the state after completion of the BR-174 as a result of the projects of the Federal Government. In general it can be said that, initially, these projects had the geopolitical vision of integrating this region the developed part of the country, and ensure official presence in this great land range. This integration would occur through the interconnection by road, which would also serve as a hub for the occupation of settlers and the future emergence of cities. The research aims to analyze the BR-174 after its recent transformations carried out by the Brazilian government, from the years 1990 and produce a critical reading of the actual purpose of the transnational corridor with the focus to the Caribbean ports and Consequently to urbanization on its axis. Observe how the connectivity of the BR-174 streamlines the state of Roraima and becomes a strategic space for its triple border: - Brazil, Venezuela, Guyana, and confront the discourse of regional development through regional integration and trans-nationalization of regional economy.